INCREASE THE EFFICIENCY OF PERSONNEL MONITORING BASED ON THE USE OF SOFTWARE - HELMAN, Valentyna; CHEREP Оleksander; BEXHTER, Lilija (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article focuses on the importance of automating certain components of the HR management system in modern companies, in particular, on the need to introduce specialised software for monitoring the work of employees, which is due to the development of the latest digital HR technologies. The study examines the characteristics, advantages and disadvantages of using employee monitoring software by modern companies. The article presents proposals for the successful use of employee monitoring software tools, which requires taking into account various motives for implementing special monitoring programmes, compliance with ethical standards and legislation, and ensuring transparency and openness in relations with employees.